PELAKSANAAN DAN STATUS HUKUM PEMBERIAN ORANG TUA KEPADA ANAK PEREMPUAN MELALUI HAREUTA PEUNULANG DI KABUPATEN ACEH BESAR - AFRIZAL AFRIZAL (PREMISE LAW JURNAL, 2015)
The inheritance system in Acehnese community who practice the parental or bilateral kinship system give equal position to their sons and daughters to be pointed as heirs. In Aceh Besar District, a daughter is not only a heir but can also receive the property granted by her parents. Hareuta Peunulang is one of the grants in the forms of jewelry, gold, home, yard or ground and so forth granted by the parents after their daughter gets married. The amount of the grant given must not greater than 1/3 (one-third) of the total number of the property of the legacy provider, and the hareuta peunulang which has been given is not returnable. A further study on granting hareuta peunulang needs to be conducted considering that the currently existing inheritance system in Aceh following Islamic inheritance system with the principle of 2:1 between the son and the daughter. The purpose of this study was to find out the existence of the grant given by the parents to their daughter through hareuta peunulang practice and to find out whether this practice of hareuta paneulang can beequated with a grant in Islamic law. Keywords: Hareuta Peunulang, Daughter, Aceh Besar